Role of early definitive management for newly diagnosed malignant pleural effusion related to lung cancer. Issue 11 (6th April 2020) - Chiang, Ka‐Yan; Ho, James Chung‐Man; Chong, Peony; Tam, Terence Chi‐Chun; Lam, David Chi‐Leung; Ip, Mary Sau‐Man; Lee, Yun‐Chor Gary; Lui, Macy Mei‐Sze
Abstract : The availability of efficacious anti‐cancer treatments, including oral targeted therapy, do not obviate the need of definitive measures for MPE in newly diagnosed lung cancer. Both early MPE control measures and cancer treatments are warranted to minimize the need of pleural re‐interventions in the course of malignancy. See related  Editorial ABSTRACT: Background and objective: The advent of effective anti‐cancer therapy has brought about uncertainty on the benefit of early definitive measures for newly diagnosed MPE from lung cancer. This study aims to investigate the outcomes of MPE in this setting. Methods: Lung cancer patients with MPE at first presentation to a tertiary care hospital were followed up till death or censored from 2011 to 2018. Early MPE control measures included chemical pleurodesis or IPC before or shortly after oncological treatment. Predictors of time to MPE re‐intervention were identified with Cox proportional hazard analyses. Results: Of the 509 records screened, 233 subjects were eligible. One hundred and twenty‐seven subjects received oral targeted therapy as first‐line treatment and 34 (26.8%) underwent early definitive MPE control measures. Early MPE control measures in addition to targeted therapy, as compared to targeted therapy alone, significantly reduced the subsequent need of MPE re‐intervention (23.5% vs 53.8%, P = 0.002). Similar benefits from MPE control measures were found in groups receiving systemic anti‐cancer therapy or best supportive care (0% vs 52%, P = 0.003; 18% vs 56.7%, P = 0.024, respectively). In the group with targetable mutations, both early MPE control measures (HR: 0.25, 95% CI: 0.12–0.53, P  < 0.001) and the use of targeted therapy (HR: 0.22, 95% CI: 0.10–0.46, P  < 0.001) were independently associated with longer time to MPE re‐interventions. Conclusion: Early MPE control measures in lung cancer has additional benefits on reducing the need and prolonging the time to MPE re‐intervention, independent of anti‐cancer therapies.